Success Stories of Established Bakeshops in Zamboanga Del Sur: A Narra-tive Inquiry - Oracion, Aljean Grace; Maghilom, Rey Christian; Anciano, Aira Jane; Batingal, Ace Virgel (Future Science / FSH-PH Publications, 2025)
The study focuses on the success stories of established bakeshops in Zamboanga del Sur. It identifies the factors that have fueled its expansion and sustainability in a competitive industry. By investigating bakery owners' experiences and strategies, the study identifies critical factors contributing to their success, providing valuable lessons for aspiring entrepreneurs and stakeholders in the bakery sector. Perseverance, dedication, and innovation play central roles in these narratives. The study further examines these bakeries' challenges, such as perishable surplus, employee behaviors, and lack of resources. Participants emphasized the value of creativity and resilience in overcoming these challenges. The owners' good character, resiliency, and leadership were critical to overcoming obstacles and achieving success. Customer satisfaction leads these bakeshops to long-term growth. These bakeries built a loyal customer base by cultivating relationships with their communities, contributing to their long-term success. This study compiles inspiring success stories and might serve as a blueprint for best practices. It emphasizes the importance of innovation, adaptability, and strong business practices in establishing and maintaining thriving bakeshops in a local setting, making it an invaluable resource for future entrepreneurs.